Mental representations and obstacles in 10-11 year old children’s thought concerning the melting and coagulation of solid substances in everyday life - Ravanis, Konstantinos (Preschool and Primary Education, 2013)
Children construct representations of concepts and physical phenomena and these representations are critical to education. For the physicist, the change of state is a transformation of matter due to the transfer of energy as heat. In several studies focused on children’s representations we find that these representations are often incompatible with the scientific model. In this research, we studied the representations of the fusion and freezing of salt and of ice and 110 children aged 10 to 11 years participated. The results of the interviews show that these children use different types of representations, the majority of which are dominated by the nature of the substance under study.